Effects of fluoride ion on the formation of earthworm‐like mesoporous silica. Issue 6 (10th April 2017) - Yang, Yuxiang; Yang, Huan; Liu, Lu; Li, Tong; Yuan, Hongmin; Ni, Chaoying
Abstract: In a strong acidic environment, ordered earthworm‐like mesoporous silica has been synthesized with CTAB templating and fluoride ion (F − ) as a counterion. The synthesized products were characterized by small‐angle X‐ray diffraction (SXRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), N2 adsorption‐desorption isotherms, and Fourier‐transform infrared spectroscopy (FTIR). The effects of F/Si mole ratio on the morphology, surface area, and the pore size of the sample were discussed. It was found that a F/Si mole ratio at 0.083 induced the formation of 3D hexagonal mesophase, whereas higher F/Si mole ratios led to the formation of 2D hexagonal mesoporous silica, the optimum molar ratio of F/Si for the formation of delicate earthworm‐like mesoporous silica was observed at 0.250. The effects of the F/Si mole ratio, surfactant chain length, acid concentration, and shear flow on morphology were also studied.